Importance of social media engagement for organizations growth: a perspective on X Solutions Limited - Hoque, Muhammed Ziaul (BRAC University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.